First stage evaluation of ISSuFiRs: Partners’ Financial Report Monitoring System by Islamic Financial Cooperatives (BMT) in Indonesia - Martiana, Andri; Yunita, Ani; Jauhari, Sobar M.; Kassim, Salina; Wong, Wing-Keung (EDP Sciences, 2023)
Most MSMEs, especially micro-enterprises, do not have good business accounting records, making it difficult for owners/managers to measure the profitability of their companies. Internal control management has a significant influence in reducing fraud in Micro Enterprises. The more principles-based accounting rules, the shorter the delay in annual reporting disclosures. It is important to have a good financial reporting system that can be utilized by Micro Enterprises and its cooperation partners who provide and distribute funds. ISSuFiRs is a web-based application that enables Islamic Financial Cooperatives to track the business progress of their financing partners. With this application, micro businesses can disclose their business activities in these financial records in accordance with the SAK-ETAP national accounting standards. Reporting on this system includes balance sheet, profit and loss, cash flow, sources, use of ZIS funds, and comments on financial reports. This study presents a prototyping framework that enables user value perception, evaluation, and continuous improvement of ISSuFiR design quality through co-creation methods. It is hoped that a simple and effective financial reporting system, ISSuFiRs, will be useful for Micro Enterprises and Islamic Financial Cooperatives to monitor business developments. This study proposes a prototyping framework that enables the user's perception of value. The framework is expected to be implemented in industrial product service systems, evaluated and then concluded. This research is ongoing, with a new prototype being rebuilt based on the evaluation results